Scanning of Genetic Variants and Genetic Mapping of Phenotypic Traits in Gilthead Sea Bream Through ddRAD Sequencing - Kyriakis, Dimitrios; Kanterakis, Alexandros; Manousaki, Tereza; Tsakogiannis, Alexandros; Tsagris, Michalis; Tsamardinos, Ioannis; Papaharisis, Leonidas; Chatziplis, Dimitris; Potamias, George; Tsigenopoulos, Costas S. (Frontiers in Genetics, 2019)
Gilthead seabream (Sparus aurata) is a teleost of considerable economic importance in Southern European aquaculture. The aquaculture industry shows a growing interest in the application of genetic methods that can locate phenotype-genotype associations with high economic impact. Through selective breeding, the aquaculture industry can exploit this information to maximize the financial yield. Here, we present a Genome Wide Association Study (GWAS) of 112 samples belonging to seven different seabream families collected from a Greek commercial aquaculture company. Through double digest Random Amplified DNA (ddRAD) Sequencing, we generated a per-sample genetic profile consisting of 2,258 high quality Single Nucleotide Polymorphisms (SNPs). These profiles were tested for association with four phenotypes of major financial importance: Fat, Weight, Tag Weight and the Length to Width ratio. We applied two methods of association analysis. The first is the typical single-SNP to phenotype test, and the second is a feature selection (FS) method through two novel algorithms that are employed for the first time in aquaculture genomics and produce groups with multiple-SNPs associated to a phenotype. In total, we identified nine single-SNPs and six groups of SNPs associated with weight related phenotypes (Weight and Tag Weight), two groups associated with Fat, and 16 groups associated with the Length to Width ratio. Six identified loci (Chr4:23265532, Chr6:12617755, Chr:8:11613979, Chr13:1098152, Chr15:3260819, Chr22:14483563) were present in genes associated with growth in other teleosts or even mammals, such as semaphorin-3A, and neurotrophin-3. These loci are strong candidates for future studies that will help us unveil the genetic mechanisms underlying growth and improve the seabream aquaculture productivity by providing genomic anchors for selection programs.